Evidence and Methods of Excavating Islamic Economic Law: Maslahah Mursalah and Its Application in Islamic Economics - Dwi Agung Ramadhan; Khaila Calsa Fhadillah; Syahrial Arif Hutagalung; Dwi Varsimutia (Haqqiyyah: Journal of Islamic and Legal Studies, 2025)
This research aims to analyze the concept of maslahah mursalah, the views of ulama on its use, and its application in various cases in the sharia financial sector, such as financing with collateral. This research shows that maslahah murlah can be a legal basis that is relevant in a modern context, maintaining sharia principles, and meeting the needs of Muslims amidst global change. Maslahah murrasa is one of the principles in Islamic law which aims to create public benefit and prevent harm without conflicting with the postulates of sharia. This principle provides legal flexibility to respond in addressing the evolving needs of society in a sharia-compliant manner, especially in the sharia economic and financial sectors.